2023
DOI: 10.18488/31.v10i1.3402
|View full text |Cite
|
Sign up to set email alerts
|

Does tourism increase energy consumption in BRICS countries?

Abstract: Tourism has been the fastest-growing sector in the world over the last decade, contributes to employment opportunities, and generates earnings in foreign currencies. Tourism intensively needs energy to promote tourist activities, which in turn causes economic growth. However, as almost all tourist activities, like hotel accommodations and transportation, strongly depend on energy use, it may contribute to increased energy consumption. Our study explores the impact of tourism on energy consumption in the BRICS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The results revealed the existence of heteroscedasticity, serial correlation, and cross-sectional dependence. In order to address these issues, the Driscoll-Kraay Standard Errors (DKSEs) [40,41], as suggested by Hoechle [42], is the preferred model for the manufacturing sector (N=9 and T=8; N is greater than T), whereas the FGLS is the preferred model for the provincial study (N=4 and T=11; T is greater than N), as suggested by the Parks-Kmenta method [35,[43][44][45]. In addition, for robustness checks, the Panel Corrected Standard Errors (PCSEs) and DKSEs are utilized.…”
Section: Methodsmentioning
confidence: 99%
“…The results revealed the existence of heteroscedasticity, serial correlation, and cross-sectional dependence. In order to address these issues, the Driscoll-Kraay Standard Errors (DKSEs) [40,41], as suggested by Hoechle [42], is the preferred model for the manufacturing sector (N=9 and T=8; N is greater than T), whereas the FGLS is the preferred model for the provincial study (N=4 and T=11; T is greater than N), as suggested by the Parks-Kmenta method [35,[43][44][45]. In addition, for robustness checks, the Panel Corrected Standard Errors (PCSEs) and DKSEs are utilized.…”
Section: Methodsmentioning
confidence: 99%
“…A tourism indicator is measured by the log of international tourists' arrivals, a commonly used proxy for tourism in the literature (Amin, Kabir, & Khan, 2020;Sarpong, Bein, Gyamfi, & Sarkodie, 2020;Ul-Haq, Imran, Oad, & Visas, 2023;Visas et al, 2023). The data is taken from World Development Indicator (WDI) dataset of the World Bank.…”
Section: Data Sources and Variable Explanationsmentioning
confidence: 99%
“…Energy is considered a key promoter of tourism (Becken, 2002;Becken, Frampton, & Simmons, 2001;Becken & Simmons, 2002;Becken, Simmons, & Frampton, 2003;Bode, Hapke, & Zisler, 2003;Gössling, 2000Gössling, , 2002Tabatchnaia-Tamirisa, Loke, Leung, & Tucker, 1997;Visas et al, 2023). Following Thai-Ha Le and Nguyen (2019), ES is measured as the ratio of energy production (in BTU) to energy consumption (in BTU).…”
Section: Data Sources and Variable Explanationsmentioning
confidence: 99%
“…The tourism industry, inter alia, has been the fastest-emerging sector across the globe over the last few decades (Visas et al, 2023). Tourism is becoming a source of economic expansion and diversification (Cattaneo, 2009).…”
Section: Introductionmentioning
confidence: 99%